Beyond the Classroom: Students’ Perspective on E-Learning Portal in Blended and Online Learning - Mohammad Nur Azhar, Mazlan; Fitri Suraya, Mohamad Hapni (UPSI Press, 2023)
Evaluating e-learning portal is essential to ensure the success of online teaching and learning activities. The portal should be assessed regularly to determine its value as a tool to support learning. This study aims to investigate students’ perspectives on using the e-learning portal as a blended and online learning activity. A survey involving two cohorts of students from a public university in Malaysia was conducted in 2016 (n = 805) and 2020 (n = 1027). The survey required the students to evaluate the use of e-Learning portal in blended and online learning, regarding their self-learning experiences, learning performances, quality of learning materials, quality of communication, and their level of interest in using the portal. The findings revealed that the majority of the students from both cohorts were generally positive about using the e-learning portal to support their learning. However, it is interesting that both cohorts preferred face-to-face instruction over online learning. Hence, future research should widen the scope of the study by analysing the perspectives of course instructors, administrators, and other relevant learning support agencies.